Servant Leadership as a Catalyst for National Development: Principles, Problems and Prospects (Journal of Management and Social Sciences, 2024)
AbstractThis paper examines the role of servant leadership as a catalyst for national development in Nigeria, highlighting its principles, challenges, and potential. It argues that the persistent issues of poverty, insecurity, and underdevelopment in Nigeria are largely attributed to ineffective leadership. The author advocates for servant leadership—characterised by empathy, listening, and community building—as a transformative approach that can address these challenges. By situating servant leadership within the context of Fountain University, the paper illustrates its practical application and the positive outcomes achieved under the administration of the current Vice Chancellor, Prof. Olayinka Ramota Karim. Additionally, the author draws parallels with historical Islamic leadership principles, emphasising that effective leadership must prioritize the well-being of the populace. The conclusion calls for a collective commitment to adopting servant leadership principles at all levels of governance to foster sustainable national development.KeywordsServant leadership, national development, Nigeria, leadership principles, Islamic leadership principles